Normal and Abnormal Behavior in Chinese Culture
XXIII, 436 p.
Keywords: Our purpose in assembling the papers in this collection is to introduce readers to studies of normal and abnormal behavior in Chinese culture. We want to offer a sense o/what psychiatrists and social scientists are doing to advance our under standing of this subject, including what fmdings are being made, what questions researched, what conundrums worried over. Since our fund of knowledge is obviously incomplete, we want our readers to be aware of the limits to what we know and to our acquisition of new knowledge. Although the subject is too vast and uncharted to support a comprehensive synthesis, in a few areas - e. g. , psychiatric epidemiology - enough is known for us to be able to present major reviews. The chapters themselves cover a variety of themes that we regard as both intrinsically interesting and deserving of more systematic evaluation. Many of the issues they address we believe to be valid concerns for comparative cross cultural studies. No attempt is made to artificially integrate these chapters, since the editors wish to highlight their distinctive interpretive frameworks as evidence of the rich variety of approaches that scholars take to this subject. 'We see this volume as a modest and self-consciously limited exploration. Here are some accounts and interpretations (but by no means all) of normal and ab normal behavior in the context of Chinese culture that we believe fashion a more discriminating understanding of at least a few important aspects of that subject.